Tim GTNN
B = \(\frac{x^2+2x+3}{x^2+2}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
`B=x^2 +y^2 -2x+4y+2010`
`=x^2 -2x+1+y^2 +4y+4+2005`
`=(x-1)^2 + (y+2)^2 +2005 >= 2005`
Dấu "=" xảy ra `<=>{(x-1=0),(y+2=0):}<=>{(x=1),(y=-2):}`
Vậy `B_(min) = 2005 <=> {(x=1),(y=-2):}`
`B=x^2+y^2-2x+4y+2010`
`B=x^2-2x+y^2+4y+2010`
`B= x^2-2.x.1+1^2-1^2 +y^2+2y.2+2^2-2^2+2010`
`B= (x^2-2x+1)+(y^2+4y+4)-1-4+2010`
`B= (x-1)^2 +(y+2)^2 +2005≥2005`
nên `B` đạt GTNN là `B=2005`
khi đó \(\left\{{}\begin{matrix}\left(x-1\right)^2=0\\\left(y+2\right)^2=0\end{matrix}\right.\) `<=>`\(\left\{{}\begin{matrix}x=1\\y=-2\end{matrix}\right.\)
B=2(x^2+2.x.1/4 +1/16)^2 -57/8
=2.(x+1/4)^2 -57/8
MinB=-57/8 khi x=-1/4
\(B=-14+2x^2+x=2\left(x^2+\dfrac{1}{2}x+\dfrac{1}{16}\right)-\dfrac{113}{8}=2\left(x+\dfrac{1}{4}\right)^2-\dfrac{113}{8}\ge-\dfrac{113}{8}\)\(ĐTXR\Leftrightarrow x=-\dfrac{1}{4}\)
\(\frac{x+2015}{5}+\frac{x+2016}{4}=\frac{x+2017}{3}+\frac{x+2018}{2}\)
\(\Leftrightarrow\left(\frac{x+2015}{5}+1\right)+\left(\frac{x+2016}{4}+1\right)=\left(\frac{x+2017}{3}+1\right)+\left(\frac{x+2018}{2}+1\right)\)
\(\Leftrightarrow\frac{x+2020}{5}+\frac{x+2020}{4}-\frac{x+2020}{3}-\frac{x+2020}{2}=0\)
\(\Leftrightarrow\left(x+2020\right)\left(\frac{1}{5}+\frac{1}{4}-\frac{1}{3}-\frac{1}{2}\right)=0\)
\(\Leftrightarrow x+2020=0\)vì \(\frac{1}{5}+\frac{1}{4}+\frac{1}{3}+\frac{1}{2}\ne0\)
\(\Leftrightarrow x=-2020\)
a) \(P=\frac{3x-9}{x^2-5x+6}-\frac{x+3}{x-2}-\frac{2x+1}{3-x}\)
\(P=\frac{3\left(x-9\right)}{\left(x-3\right)\left(x-2\right)}-\frac{x+3}{x-2}-\frac{2x+1}{3-x}\)
\(P=\frac{3}{x-2}-\frac{x+3}{x-2}-\frac{2x+1}{3-x}\)
\(P=\frac{3\left(3-x\right)-\left(x+3\right)\left(3-x\right)-\left(2x+1\right)\left(x-2\right)}{\left(x-2\right)\left(3-x\right)}\)
\(P=\frac{9-3x-9+x^2-2x^2+4x-x+2}{\left(x-2\right)\left(3-x\right)}\)
\(P=\frac{2-x^2}{\left(x-2\right)\left(3-x\right)}\) (*)
b) Thay \(x=-\frac{1}{2}\) vào (*) ta có:
\(P=\frac{2-\left(-\frac{1}{2}\right)^2}{\left[\left(-\frac{1}{2}\right)-2\right]\left[3-\left(-\frac{1}{2}\right)\right]}=\frac{2-\frac{1}{4}}{-\frac{5}{2}.\frac{7}{2}}=-\frac{\frac{7}{4}}{\frac{5}{2}.\frac{7}{2}}=-\frac{7}{35}=-\frac{1}{5}\)
c) \(\frac{2-x^2}{\left(x-2\right)\left(3-x\right)}< 0\)
\(\Leftrightarrow2-x^2< 0\)
\(\Leftrightarrow-x^2< -2\)
\(\Leftrightarrow x^2>2\)
\(\Leftrightarrow\hept{\begin{cases}x< -\sqrt{2}\\-\sqrt{2}< x< \sqrt{2}\\x>2\end{cases}}\)
Vậy: ...
x=0 còn B=1